Pharmaceutical Co-Crystallization: Strategies for Co-Crystal Design: Pharmaceutics - Devi, Preeti; Budhwar, Vikas; Kakkar, Saloni; Kumar, Ashwani (International Journal of Life Science and Pharma Research, 2023)
Pharmaceutical co-crystal belongs to a subtype of crystal in which one component is an active pharmaceutical ingredient (API) and the other is coformer (generally regarded as safe GRAS). In the crystal lattice, the two components are hydrogen-bonded in a fixed stoichiometric ratio. Co-crystallization is a cheap and simple alternative to the presently available techniques of solubility enhancement and has gained much interest from the formulators during the recent few years. Because co-crystals can enhance the physiochemical properties of pharmaceuticals without affecting their therapeutic effect, the area of pharmaceutical co-crystals has reached a tipping point. Besides increasing solubility, some more applications of co-crystals have also been identified to enhance physicochemical properties like permeability, bioavailability, stability, tablet ability, etc. Co-crystals have been extensively studied in the literature, and there is a tremendous amount of literature on co-crystals. However, an exhaustive review of coformer selection and co-crystal regulation must be included. An effort has been made in the review to fill this void. The current study focuses on how co-crystallization can enhance the pharmaceutical characteristics of different drugs, besides giving an overview of the historical background and landmarks in discovering co-crystals. In this review paper, we have discussed the rational design of co-crystals and the selection of conformers for the synthesis of multi-component co-crystals, methods like H-bonding, PKa value, Synthonic engineering, Cambridge structural database, Hansen solubility parameter (HSP), etc as well as the IPR related details all across the world. There is an attempt to include reported works on co-crystals, which helps understand the concept. This review paper discusses pharmaceutical regulatory bodies in the US and Europe released guidelines that are highly useful for pharmaceutical product registration in these regions. Here, we also examine various commercially available pharmaceutical drug products. It also briefly predicts the future perspective of co-crystallization.